Pengaruh Peran Ganda Stres Kerja dan Beban Kerja Terhadap Kinerja Pegawai Wanita UPTD Puskesmas Ngadiluwih - Erinda Dita Ayu Putri; Sonny Subroto; Nuril Aulia Munawaroh (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research is motivated by a company engaged in the agency. The purpose of this study was to explain the effect of dual roles, work stress and workload on the performance of female employees. This research was conducted at UPTD Puskesmas Ngadiluwih. This research method used is a quantitative method using questionnaires as data. This research uses purposive sampling technique. The sample in this study were all female employees as many as 30 employees of UPTD Puskesmas Ngadiluwih. the technique used to analyze is with the SPSS IMB version 27 program. Data analysis techniques in this study with validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, f test and R2 determination coefficient test. The results of this test concluded that the t test showed that the dual role variable partially had a significant positive effect on employee performance with a significant value of <0.001 and a tcount value of 3.874. The work stress variable partially has a non-significant positive effect on employee performance with a significant value of 0.065 and a tcount value of 1.925. The workload variable partially has a positive and insignificant effect on employee performance with a significant value of 0.932 and a tcount value of -0.086. And the results of the f test show that the dual role variable, work stress and workload have a significant effect on the performance of female employees with a significant value of <0.001 and a Fcount of 18,145 .